EvonHowell
  • EvonHowell
6 (3-x) = -4 (2x-1) Find x Value The X Value is 7 or -7 just can't figure out how to get the answer
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
EvonHowell
  • EvonHowell
And I got alot more of this crap and my teacher didn't tell me how to do them
anonymous
  • anonymous
6(3- x) = -4(2x - 1) the first thing you want to do is distribute the 6 and the -4 through the parenthesis. Can you do that ?
EvonHowell
  • EvonHowell
I know what distribute means but don't know how to do it exactly

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
6(3 - x) = 6 * 3 - 6 * x and -4(2x - 1) = -4 * 2x - (-4) * 1 understand ?
anonymous
  • anonymous
let me restate that second one....-4 * 2x + -4 * -1
EvonHowell
  • EvonHowell
soo 12x = 13x?
anonymous
  • anonymous
6(3 - x) = -4(2x - 1) 18 - 6x = -8x + 4 can you take it from here because I have to go...sorry
anonymous
  • anonymous
18 - 6x = -8x + 4 subtract 18 from both sides -6x = -8x + 4 - 18 -6x = -8x - 14 now add 8x to both sides -6x + 8x = -14 2x = -14 x = -7 sorry I couldn't explain better, I have to go now
EvonHowell
  • EvonHowell
-6x - 90 = 9x
EvonHowell
  • EvonHowell
Tho I am so lost with all this stuff
thomaster
  • thomaster
subtract 9x on both sides and add 90 on both sides You'd get -15x=90 now divide by -15
thomaster
  • thomaster
The point is that you bring the variables (x in this case) to the left side of the equation, and the numbers to the right side.
EvonHowell
  • EvonHowell
-6 is the answer?
thomaster
  • thomaster
\(\large\dfrac{~~90}{-15}=-6\) so yea
EvonHowell
  • EvonHowell
so whats about 3x - 4 = 10-4x How would i do this one
thomaster
  • thomaster
bring numbers to the right, x to the left. To bring x to the left, you would have to add 4x on both side. That way, you can cancel the -4x on the right. \(\large3x - 4 = 10-4x\) \(\large3x~\underline{+4x} - 4 = 10-4x~\underline{+4x}\) \(\large7x - 4 = 10\)
thomaster
  • thomaster
Now you only have to bring -4 to the right Just add 4 on both sides and you'll cancel the -4 on the left. So it'll become: 7x=14 now you divide 14 by 7 to solve for x
EvonHowell
  • EvonHowell
x=2
thomaster
  • thomaster
exactly :)
EvonHowell
  • EvonHowell
can we do 2 more?
thomaster
  • thomaster
sure
EvonHowell
  • EvonHowell
-7 - (-4x) = -4x+9
EvonHowell
  • EvonHowell
oops 2 more after this 1 my bad
thomaster
  • thomaster
Alright first of all: -(-4x) is the same as +4x
thomaster
  • thomaster
So the equation would be -7 +4x = -4x+9
thomaster
  • thomaster
now we want that -7 on the other side of the equation, so we add 7 on both sides 4x=-4x+16
thomaster
  • thomaster
last thing is to add 4x on both sides to get that -4x to the left 8x=16 Do you know what to do now?
EvonHowell
  • EvonHowell
Divide both sides by 8?
thomaster
  • thomaster
Yep :)
EvonHowell
  • EvonHowell
x=2
thomaster
  • thomaster
correct
EvonHowell
  • EvonHowell
|dw:1378003846241:dw|
thomaster
  • thomaster
We first want to get rid of the fractions. To do that, multiply everything with the denominator. They're both 10 here so we can multiply everything with 10
EvonHowell
  • EvonHowell
30x= 7-70x?
thomaster
  • thomaster
\(\Large\sf\dfrac{3}{10}*10=\ ?\)
EvonHowell
  • EvonHowell
3?
thomaster
  • thomaster
Yep, also don't forget to multiply 7 by 10
EvonHowell
  • EvonHowell
3x=70-7x?
thomaster
  • thomaster
yes :) Do you know what to do next?
EvonHowell
  • EvonHowell
-7x from both sides?
thomaster
  • thomaster
there already is a -7x on the right side. you won't cancel it out with you subtract 7x... it would be 3x = 70 -14x then
EvonHowell
  • EvonHowell
ok then idk.
thomaster
  • thomaster
You don't subtract the 7x, you have to add it to both sides :)
EvonHowell
  • EvonHowell
ooh ok
thomaster
  • thomaster
because -7x + 7x = 0 It would dissapear on the right side of the equation
EvonHowell
  • EvonHowell
9x=70
EvonHowell
  • EvonHowell
then divide by 9
thomaster
  • thomaster
3+7 = 9?
EvonHowell
  • EvonHowell
oops 10
EvonHowell
  • EvonHowell
so x=10
thomaster
  • thomaster
No 10x = 70
EvonHowell
  • EvonHowell
yes 10x=7- then divide by 10 the tens on the left would cancel leaveing 70/10 which would diide into 10 soooo x=10
EvonHowell
  • EvonHowell
70* for the first part sorry
thomaster
  • thomaster
70/10 = ?
EvonHowell
  • EvonHowell
oh dear god x=7 i'm stupid
thomaster
  • thomaster
haha just small mistakes :) happens to the best
EvonHowell
  • EvonHowell
LAST ONE!! 1/6 (6-x) = 27 + 2x
thomaster
  • thomaster
\(\large\dfrac{1}6(6-x)=27+2x\) Any idea how to get rid of that fraction?
thomaster
  • thomaster
Oh wait
thomaster
  • thomaster
First distribute it :)
EvonHowell
  • EvonHowell
How do I distribute a fraction again?
thomaster
  • thomaster
so \((\dfrac{1}6 * 6)-(\dfrac{1}6*x)\)
thomaster
  • thomaster
|dw:1378005185572:dw|
EvonHowell
  • EvonHowell
uh..
thomaster
  • thomaster
\(\large\sf\dfrac{1}6*6=\ ?\)
EvonHowell
  • EvonHowell
1
EvonHowell
  • EvonHowell
i think i have no clue but think it is 1
thomaster
  • thomaster
Yes, And \(\large\sf\dfrac{1}6*x=just\ \dfrac{1}6x\)
thomaster
  • thomaster
So now that you have distributed the 1/6, The equation would be: \(\Large\sf1-\dfrac{1}6x=27+2x\)
thomaster
  • thomaster
Now we can get rid of the fraction by multiplying everything by 6
EvonHowell
  • EvonHowell
soo 1-6x=27+2x ooorrr 6x=27+2x
thomaster
  • thomaster
Multiply everything by 6, what do you get?
EvonHowell
  • EvonHowell
6x=27+2x? I'm lost now
thomaster
  • thomaster
Just multiply every individual part by 6 So 1*6 = 6 1/6x * 6 = 1x 27*6=162 2*6=12 So now you'd have: \(\Large\sf6-x=162+12x\)
thomaster
  • thomaster
Do you know what to do now?
EvonHowell
  • EvonHowell
subtract 12 from both sides??
thomaster
  • thomaster
exactly
thomaster
  • thomaster
actually subtract 12x
EvonHowell
  • EvonHowell
so than that would go to -6=162?
EvonHowell
  • EvonHowell
or -6x?
thomaster
  • thomaster
-x-12x=?
EvonHowell
  • EvonHowell
-12x? o.O
thomaster
  • thomaster
|dw:1378006268757:dw|
thomaster
  • thomaster
it's the same as -1-12, it would be -13
EvonHowell
  • EvonHowell
so -13=162??
thomaster
  • thomaster
Don't forget about the 6 in front of -13\(\large\sf x\)
thomaster
  • thomaster
6-13x=162
EvonHowell
  • EvonHowell
ok i would subtract 13x from 6?
thomaster
  • thomaster
you can't subtract a variable from a number... You'd have to subtract 6 from both sides
EvonHowell
  • EvonHowell
so 13x=156
thomaster
  • thomaster
-13x=156
EvonHowell
  • EvonHowell
yeahh my bad so dived by -13 the -13 on the left would cancel out so x=-12
thomaster
  • thomaster
That's correct :) great job
EvonHowell
  • EvonHowell
Thank You!!!!!! Ok now i'm done with my math thanks soo much!!
thomaster
  • thomaster
No problem \(\LARGE\ddot\smile\)

Looking for something else?

Not the answer you are looking for? Search for more explanations.